PENGARUH RETRUN ON INVESMENT (ROI) DAN PRICE EARNING RATIO TERHADAP HARGA SAHAM PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR BI BURSA EFEK INDONESIA BEI PADA PERIODE 2011- 2014 - Fhartika Diana Mentari; Lena Farida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
In examining the effect of return on investment as (ROI) and price earnings ratio (PER) on stock prices on food and beverage companies listed on the Stock Exchange will be used by several variables: the first is Return On Investment (ROI) that is how many the ability of the company's overall generating profits in the aggregate assets tersedian within the company, it is for investors to see how far the company's ability to manage their own capital to generate net income. The second is the price earnings ratio (PER) provides an overview of the company's ability to determine the price of shares. In this study aims to test whether the effect of the Return on investmean (ROI) Dan Price earning ratio (PER) on stock prices on food and beverage companies that have been listed in the Indonesia Stock Exchange (BEI) by taking a sample of 4 year study period, namely in 2011- 2014. Samples were used as research material there are five companies of drinks and food are equally listed since 1994 on the Indonesian Stock Exchange (BEI) although this study only in grab samples but is expected to serve as a reference and a general description of one of the companies that have been listed in ( BEI). Data analysis technique used is multiple linear regression and hypothesis testing using t test. And f test the conclusions of this study are variable ROI have a significant effect on stock prices and PER variables influence the stock price, to test the effect of ROI, PER and stock prices with SPSS memggunakan formula Keyword : ROI, PER, and On Stock Prices